The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/psp4.12858
|View full text |Cite
|
Sign up to set email alerts
|

Model enhanced reinforcement learning to enable precision dosing: A theoretical case study with dosing of propofol

Abstract: Extending the potential of precision dosing requires evaluating methodologies offering more flexibility and higher degree of personalization. Reinforcement learning (RL) holds promise in its ability to integrate multidimensional data in an adaptive process built toward efficient decision making centered on sustainable value creation. For general anesthesia in intensive care units, RL is applied and automatically adjusts dosing through monitoring of patient's consciousness. We further explore the problem of opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The proposed RL-approach was developed with this aim. Indeed, differently from the previous works 26,28,30 where the objective was the identification of an optimal dosing strategy for an entire patient population, here, the scope of the RL-approach was to individually optimize the erdafitinib adaptive dosing protocol by tailoring the dose adjustment rules on each patient. In the RL-context, this change of perspective means to move from a unique RL-agent, trained on an entire patient population, to a set of personal QL-agents, each trained on a single individual patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed RL-approach was developed with this aim. Indeed, differently from the previous works 26,28,30 where the objective was the identification of an optimal dosing strategy for an entire patient population, here, the scope of the RL-approach was to individually optimize the erdafitinib adaptive dosing protocol by tailoring the dose adjustment rules on each patient. In the RL-context, this change of perspective means to move from a unique RL-agent, trained on an entire patient population, to a set of personal QL-agents, each trained on a single individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, a number of recent works has promoted the idea of coupling RL algorithms with population PK-PD modeling. 21,23,25,26 In this context, PK-PD models were used to simulate virtual patients and, thus, to generate experience from different dosing scenarios on which the RL algorithm could learn the optimal dosing strategy. In almost all the works reported in the literature, a unique RLagent was trained to find an optimal dosing strategy for an entire patient population.…”
Section: Reinforcement Learning and Pk-pd Models Integration To Perso...mentioning
confidence: 99%
“…Optimal dosing of propofol administration (Ribba et al, 2022) Just-in-time-adaptive-intervention for HeartSteps, mobile app aimed at reducing physical inactivity (Liao et al, 2020) Population analysis of signal-detection task in anhedonic subjects (Huys et al, 2013) between digital health applications and pharmacological drugs represents a ground for attempting to reframe PMX-a recognized key player in the development of the latter-as a key support to the development of the former, in particular when it comes to precision dosing for digital health.…”
Section: Study Case [References]mentioning
confidence: 99%
“…We have recently evaluated the performance of RL algorithms for precision dosing of propofol for general anesthesia and for which a meta-analysis showed that the monitoring of the bispectral index (BIS)-a PD endpoint-contributes to reduce the amount of propofol given and the incidence of adverse reactions (Wang et al, 2021). In (Ribba et al, 2022), we performed a theoretical analysis of propofol precision dosing confronting RL to hallmarks of clinical pharmacology problems during drug development, i.e. the low number of patients and tested dosing regimen, the incomplete understanding of the drivers of response and the presence of high variability in the data.…”
mentioning
confidence: 99%
“…13 Extension of such application for patient care include exploration of novel AI/ML method, such as reinforcement learning for precision dosing in individual patients. 14 One of the most exciting prospects lies in using AI/ML in model-informed drug development. The potential for high impact in this area is immense and is currently an active domain of research.…”
Section: Artificial Intelligence -Potential Applications In the Pharm...mentioning
confidence: 99%